Tryptophan and Cysteine Mutations in M1 Helices of α1β3γ2L γ-Aminobutyric Acid Type A Receptors Indicate Distinct Intersubunit Sites for Four Intravenous Anesthetics and One Orphan Site. (December 2016) - Nourmahnad, Anahita; Stern, Alex T.; Hotta, Mayo; Stewart, Deirdre S.; Ziemba, Alexis M.; Szabo, Andrea; Forman, Stuart A.
Abstract : Background: γ-Aminobutyric acid type A (GABAA ) receptors mediate important effects of intravenous general anesthetics. Photolabel derivatives of etomidate, propofol, barbiturates, and a neurosteroid get incorporated in GABAA receptor transmembrane helices M1 and M3 adjacent to intersubunit pockets. However, photolabels have not been consistently targeted at heteromeric αβγ receptors and do not form adducts with all contact residues. Complementary approaches may further define anesthetic sites in typical GABAA receptors. Methods: Two mutation-based strategies, substituted tryptophan sensitivity and substituted cysteine modification–protection, combined with voltage-clamp electrophysiology in Xenopus oocytes, were used to evaluate interactions between four intravenous anesthetics and six amino acids in M1 helices of α1, β3, and γ2L GABAA receptor subunits: two photolabeled residues, α1M236 and β3M227, and their homologs. Results: Tryptophan substitutions at α1M236 and positional homologs β3L231 and γ2L246 all caused spontaneous channel gating and reduced γ-aminobutyric acid EC50 . Substituted cysteine modification experiments indicated etomidate protection at α1L232C and α1M236C, R -5-allyl-1-methyl-5-( m -trifluoromethyl-diazirinylphenyl) barbituric acid protection at β3M227C and β3L231C, and propofol protection at α1M236C and β3M227C. No alphaxalone protection was evident at the residues the authors explored, and none of the tested anesthetics protected γ2I242C or γ2L246C. Conclusions: All five intersubunit transmembrane pockets of GABAA receptors display similar allosteric linkage to ion channel gating. Substituted cysteine modification and protection results were fully concordant with anesthetic photolabeling at α1M236 and β3M227 and revealed overlapping noncongruent sites for etomidate and propofol in β + –α – interfaces and R -5-allyl-1-methyl-5-( m -trifluoromethyl-diazirinylphenyl) barbituric acid and propofol in α + –β – and γ + –β – interfaces. The authors' results identify the α + –γ – transmembrane interface as a potentially unique orphan modulator site. Abstract : Complementary structure–function studies involving site-directed mutagenesis of amino acid residues lining the five predicted intersubunit binding pockets in a typical γ-aminobutyric acid type A receptor show that four intravenous anesthetics have distinct but overlapping patterns of interaction with the receptor. These findings validate previous anesthetic photolabeling findings and further define the properties of the distinct sites that mediate the potentiating effects of various intravenous anesthetics with γ-aminobutyric acid type A receptors.